Bleeding events in patients with cardiac amyloidosis. (25th November 2020) - Schrutka, L; Avanzini, N; Seirer, B; Rettl, R; Dachs, T; Duca, F; Binder, C; Dalos, D; Badr Eslam, R; Bonderman, D
Abstract: Background: Amyloid cardiomyopathy (CA) is a life-threatening disease that arises from the accumulation of insoluble fibrous deposits of misfolded proteins in the myocardium. Infiltration of the conduction system results in a high prevalence of atrial fibrillation (AF). Due to a notable thromboembolic risk, long-term anticoagulation is preferred once AF is detected in amyloidosis. However, anticoagulation may exacerbate the hemorrhagic tendency, previously described in amyloid light-chain (AL) amyloidosis. Therefore, the potential benefits of anticoagulation must be carefully weighed against hemorrhagic complications. Methods: We recorded bleeding events in a prospective cohort of CA patients. Results: Out of 140 patients (median age of 73 years (IQR 62–77) and 77.1% of male gender) 65 (46.4%) were diagnosed with AL amyloidosis and 69 (49.3%) had transthyretin amyloid deposits (ATTR). Median NYHA functional class was 3 (IQR 2–3) and NT-proBNP 2574 pg/mL (1070–7173). 42.1% of patients (n=59) were treated with OAC with 13 (22.0%) receiving vitamin-K-antagonists (VKA) and 46 (78.0%) novel oral anticoagulants (NOACS). During a median follow up time of 23 months (IQR 9–35) 22 bleeding events occurred. In total, we recorded 1 cerebral bleeding, 7 gastrointestinal bleedings, 8 urogenital bleedings, 4 hematomas and 2 nasal bleedings. Of those, fifteen (68.2%) were observed in orally anticoagulated patients (p=0.198). 4 (30.8%) bleeding events occurred in the VKA treated group and 11 (23.9%) under NOAC treatment (p=0.335). Bleeding events were more prevalent in patients with AL compared to TTR amyloidosis (14, 63.6% vs 8, 36.4%, p=0.011). No difference was observed in terms of CHA2DS2-VASc score: 4 (IQR 2–5) in the bleeding group versus 3 (IQR 1–4) in the control group (p=0.579). On the contrary, HASBLED score was higher in patients with bleeding events: 4 (IQR 4–5) versus 2 (IQR 1–3) (p<0.001). Patients with bleeding events had a higher prevalence of arterial hypertension (p=0.010) and chronic kidney disease (p=0.002). Overall survival was comparable between the groupss (Figure 1). Conclusion: Although CA is associated with potentially life-threatening hemorrhage, our cohort did not reveal a higher prevalence of fatal bleeding in patients treated with oral anticoagulation. Patients who experienced bleeding events did not show worse outcomes. Funding Acknowledgement: Type of funding source: None